Transmission Performance Research of Digital Modulation Signals in AWGN Channel - Jianbin Xue; Songbai Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
As mainstream of wireless communication system,digital communication system cannot directly transmit digital baseband signals that must be modulated at the sender before being sent into wireless channel.Digital modulation that is using baseband signals to control the parameters of carrier, includes amplitude modulation, frequency modulation and phase modulation.Noise existing in wireless channel can seriously affect signal’s transmission performance.AWGN (additive white Gaussian noise) channel is the most simple radio channel, this paper aims at transmission performance analysis of three kinds of digital modulation signals in AWGN channel and comparing the simulation value with theoretical value that’s not affected by AWGN,the idea proposed in this paper includes four ways that cover the comparison between simulated BER(bit error rate) and theoretical BER,simulated SER(symbol error rate) and theoretical SER,the simulation results show the difference about transmission performance of modulated signals with or without AWGN. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2065